Chronic urinary tract infections in patients with spinal cord lesions – biofilm infection with need for long‐term antibiotic treatment. Issue 4 (April 2017) - Tofte, Nete; Nielsen, Alex C. Y.; Trøstrup, Hannah; Andersen, Christine B.; Von Linstow, Michael; Hansen, Birgitte; Biering‐Sørensen, Fin; Høiby, Niels; Moser, Claus
Abstract : Patients suffering from spinal cord injuries resulting in complete or incomplete paraplegia or tetraplegia are highly disposed to frequent, recurrent or even chronic urinary tract infections (UTIs). The reason for the increased risk of acquiring UTIs is multifactorial, including reduced sensation of classical UTI symptoms, incomplete bladder emptying, frequent catheterizations or chronic urinary tract catheters. Biofilms in relation to UTIs have been shown both on catheters, on concrements or as intracellular bacterial communities (IBCs). Due to the increased risk of acquiring recurrent or chronic UTIs and frequent antibiotic treatments, patients experience an increased risk of being infected with antibiotic‐resistant bacteria like extended‐spectrum β‐lactamase–producing Escherichia coli or Klebsiella spp., but also bacteria like Pseudomonas aeruginosa inherently resistant to several antibiotics. Diagnosing the UTI can also be challenging, especially distinguishing harmless colonization from pathogenic infection. Based on a previous study showing activation of humoral immune response toward UTI pathogens in patients with spinal cord lesions (SCL), the present mini review is an evaluation of using antibody response as an indicator of chronic biofilm UTI. In addition, we evaluated the effect of long‐term treatment with antibiotics in patients with SCLs and chronic UTI, defined by culturing of a uropathogen in the urine and elevated specific precipitating antibodies against the same uropathogen in a blood sample. Elimination of chronic UTI, decrease in specific precipitating antibody values and avoiding selection of new multidrug‐resistant (MDR) uropathogens were the primary markers for effect of treatment. The results of this evaluation suggest that the long‐term treatment strategy in SCL patients with chronic UTI may be effective; however, randomized prospective results are needed to confirm this.